Generation of landomycin D-producing strain Streptomyces globisporus LD3 - Ostash, B; Kozarevska, I; Fedorenko, V (Folia microbiologica, 2005)
Rhodinosyl transferase gene lndGT4, governing the conversion of the disaccharide oligoketide ('polyketide') landomycin D into a trisaccharide derivative landomycin E, was deleted in Streptomyces globisporus 1912 genome. Possible resistance mechanisms that protect the resulting landomycin D-producing mutant strain S. globisporus LD3 against the toxic action of landomycins were determined.
Keywords: testy genetické komplementace; Drug Resistance, Bacterial; antibakteriální látky; delece genu; Aminoglycosides; Transferases; glykosylace; Genes, Bacterial; Glycosylation; Genetic Complementation Test; Anti-Bacterial Agents; transferasy; bakteriální léková rezistence; Gene Deletion; bakteriální geny; Streptomyces; aminoglykosidy